A method to measure the eco-efficiency of diesel locomotive. (March 2017) - Carvalhaes, Bernardo Bicalho; Rosa, Rodrigo de Alvarenga; D'Agosto, Márcio de Almeida; Ribeiro, Glaydston Mattos
Highlights: A railroad's eco-efficiency measurement method is proposed. Seven eco-efficiency indicators were proposed. The methodology was applied to a real major Brazilian railroad. Results achieved by the proposed method were compared with USA EPA standards. Different alternative fuels and technologies were evaluated. Abstract: Brazilian railroads transport over 490 million tons a year using diesel-electric locomotives. These locomotives emit several pollutants into the atmosphere and because of that, the railroads seek to reduce emissions and achieve global emission standards. Thus, it is important to analyze the environmental impact of the use of diesel and alternative fuels to reach environmental standards. This paper makes use of a method based upon the World Business Council for Sustainable Development (WBCSD) metrics to evaluate the locomotives' eco-efficiency. The method was applied to Estrada de Ferro Vitória a Minas (EFVM). Different scenarios representing the exchange of fuel sources and technologies were developed, tested and analyzed. The impacts were evaluated by seven eco-efficiency performance indicators and compared with United States Environmental Protection Agency (EPA) standards. The results offered cost savings and emissions reduction opportunities.